On the Rotor Stator Interaction Effects of Low Specific Speed Francis Turbines - Einar Agnalt; Igor Iliev; Bjørn W. Solemslie; Ole G. Dahlhaug (International Journal of Rotating Machinery)
The rotor stator interaction in a low specific speed Francis model turbine and a pump-turbine is analyzed utilizing pressure sensors in the vaneless space and in the guide vane cascade. The measurements are analyzed relative to the runner angular position by utilizing an absolute encoder mounted on the shaft end. From the literature, the pressure in the analyzed area is known to be a combination of two effects: the rotating runner pressure and the throttling of the guide vane channels. The measured pressure is fitted to a mathematical pressure model to separate the two effects for two different runners. One turbine with 15+15 splitter blades and full-length blades and one pump-turbine with six blades are investigated. The blade loading on the two runners is different, giving different input for the pressure model. The main findings show that the pressure fluctuations in the guide vane cascade are mainly controlled by throttling for the low blade loading case and the rotating runner pressure for the higher blade loading case.